PHYSICAL SOIL ATTRIBUTES IN DIFFERENT EUCALYPTUS CROP MANAGEMENT SYSTEMS IN WESTERN MATO GROSSO, BRAZIL - Florentim, Elyson Thiago de Souza; Correa, Helen Caroline Rodrigues; Martins, Paloma Emanuela Braga; Silva, Fulvianny Cristina da; Zeviani, Walmes Marques; Serafim, Milson Evaldo (Floresta, 2020)
Physical soil attributes in different eucalyptus crop management systems in western Mato Grosso, Brazil. The aim of this study was to determine the effect of four soil management systems on the physical attributes of an Oxisol for Eucalyptus crops in western Mato Grosso, Brazil. The management systems are differentiated by the soil preparation form during the implantation and initial forest establishment phases, namely a conventional system (plowing, harrowing and subsoiling for preparation and harrows for weed control after planting ) and a conservationist system (pasture desiccation, subsoiling, herbicide weed control and cover crop), with added differences in the eucalyptus fertilizer supply manner (haul and furrow). Nine soil layers were sampled continuously for each management system in between the sowing lines using 100 cm³ volumetric rings (0.05 m in diameter and height), totaling a studied layer of 0.45 m. The following variables were evaluated: total pore volume, microporosity, macroporosity, density and soil resistance to penetration. The different managements did not lead to significant differences for the studied attributes two years after forest establishment, with only a small depth effect observed. The attribute values are within the appropriate limits for eucalyptus crop development, indicating good soil quality under the eucalyptus forest for the study conditions. Keywords: Cover crop, Eucalyptus, soil management, soil penetration resistance.